Radiological Aspects of Temporo-Mandibular Joint Osteoarthritis (Texas Journal of Medical Science, 2024)
This article is about applications of computed tomography (CT) in diagnosis of inflammatory and degenerative disease of temporomandibular joint (TMJ). CT is highly informative method forvisualization of disease of temporomandibular joint. Finally, sections on other aspects of CT research related to the TMJ, clinical decision-making and concluding remarks are added. However, it should be emphasized that the diagnostic information obtained is limited to the morphology of the osseous joint components, cortical bone integrity and subcortical bonedestruction/production. Author of this research studied the frequency of radiological signs in different age group. In addition, there were studied frequency of isolated, combination types, and more and less localization sitesof radiological patterns of inflammatory and degenerative changes of temporo-mandibular joint